Investigations in the food-energy-water nexus: the effects of mixed wettability on soil evaporation and the feasibility of using nuclear microreactor process heat for concurrent bioconversion and agricultural practices - Pakkebier, Jack (Kansas State University, 2024)
Food, energy, and water are inherently connected. The Ogallala Aquifer, a primary irrigation water source in the High Plains region of the U.S., is declining, thereby necessitating new water conservation strategies. Meanwhile, there is also a global goal to achieve a 43% reduction in global greenhouse gas emissions by 2030, relative to the levels recorded in 2019. These problems are separate yet still interconnected. The work of this thesis poses solutions in which these problems may be alleviated. First, this thesis investigates the impacts of mixed wettability on the evaporation dynamics of a 10-µL sessile water droplet placed within simulated soil pores comprised of hydrophobic Teflon beads (CA ~ 108°) and hydrophilic glass (CA ~ 41°) beads with 2.38-mm diameters, where homogeneous and heterogeneous (i.e., mixed hydrophobicity and hydrophilicity) wettability configurations were investigated. Mixed wettability was of particular interest due to the possibility of reaping the lengthened evaporation times of hydrophobic materials while also having the advantages of decreased runoff and enhanced infiltration attributed to hydrophilic materials. Experiments were performed in an environmental chamber where the relative humidity and temperature were 60%±0.1% RH and 20°C±0.4°C, respectively. Wettability influenced evaporation times, with homogeneous hydrophobic pores (i.e., three Teflon beads) and heterogeneous one glass, two Teflon pores having the longest average evaporation times of 40 and 39 minutes, respectively. Homogeneous hydrophilic pores (i.e., three glass beads) and heterogeneous two glass, one Teflon pores exhibited evaporation times of 34 minutes. Evaporation times for heterogeneous combinations trended based on the predominant wettability. Contact angles and the projected length of contact were analyzed from videos to capture pinning and depinning during evaporation. For many measurements on hydrophobic beads, contact angles were less than 90°, and in some configurations, water would be pinned on a Teflon bead while depinning (i.e., moving) on a glass bead. Stick-slip evaporation was observed, where the evaporating droplet switched between constant contact radius (CCR) and constant contact area (CCA) evaporative modes to minimize droplet surface energy. The results suggest wettability alterations in agricultural settings may reduce evaporation. For the next portion of the thesis, the feasibility of using nuclear microreactor process heat for bioconversion and agricultural processes is investigated. Nuclear microreactors, a subset of small modular reactors, offer promise in addressing climate challenges due to their compact size, ease of deployment, and potential for carbon-neutral power generation. Operational conditions and requirements of bioconversion and agricultural methods (e.g., gasification, pyrolysis, hydrothermal carbonization, hydrothermal liquefaction, hydrothermal gasification, ethanol production, anaerobic digestion, and pasteurization) are obtained from a brief literature review. Next, a Brayton cycle model with a regenerator and air as the working fluid, based on the eVinci microreactor design, was developed to assess the feasibility of powering these processes using nuclear microreactor heat. Exergetic efficiency values were calculated to match process heat values with operational temperatures, where high-temperature processes such as gasification and pyrolysis demonstrated efficiencies of 72-100% and lower-temperature processes such as pasteurization and anaerobic digestion ranged from 2-53%, depending on the microreactor design. There were tradeoffs between producing net power and utilizing process heat, particularly for high-temperature processes; three different heat exchanger locations were considered. Results show that high-temperature processes [e.g., gasification (600℃ at minimum)] require too high of temperatures to be feasible based on the model. Some processes (e.g., ethanol production, hydrothermal carbonization, and hydrothermal liquefaction) are more suited to a heat exchanger located between the turbine and regenerator, but can also be run before the turbine. Lower temperature processes, like pasteurization and anaerobic digestion, can utilize waste heat after the regenerator and, therefore, do not impact power production.
Keywords: Mixed-wettability; Evaporation; Stick-slip; Microreactor; Carbon-neutral; Biofuels